Innovation design school uniform for disable children in primary school / Lilinieta Talib … [et al.] - Talib, Lilinieta; Mansor, Hairul Nizam; Khalid, Rafidah; Mustafa, Muhammad Khalik; Mustapha, Shahrizat Fitri (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2013)
In Malaysia school uniform are compulsory for all students who attend government or public schools. The school uniform for government primary school is white color for top and navy blue color for bottom. For boys the top is white shirt and long navy-blue trousers since the choice between long or short trousers for boys, in recent times it has become more common for Muslim boys to wear long trousers. For girls they wear Navy blue pinafore over white shirt or White baju kurung (a long tunic that covers the arms) over long navy-blue skirt. This project innovation is to reveal new design in product development for disable children, we design the uniform according for functionality, and attractive, easy to use, affordable price and safety are all attributes that are expected in daily wear uniform. By using traditional school uniform for primary school, we construct few product lines will be design for the disable people. We construct the design, mainly the clothes opening are re-construct for the purpose of easy wear concepts for the disable and functionality of the uniform for easy to move but still look attractive and can be acceptable among the school community society. The main identification on designing the clothes involve with the opening, length and shape. The product enables the maximum functions for the disable user.